THE INFLUENCE OF BRAND IMAGE AND BRAND TRUST ON BRAND LOYALTY AMONG VIVO SMARTPHONE USERS IN CIREBON - M. Sarudin; Muhammad Santoso; Soesanty Maulany (RADJA PUBLIKA, 2026)
This study aims to determine and analyze the influence of brand image and brand trust on brand loyalty among VIVO smartphone users in Cirebon. This research used quantitative research. The sample size was 170 respondents. The data analysis method used was multiple linear regression analysis. Based on the results of the t-test, it can be concluded that brand image has a significant effect on brand loyalty, with a calculated t-value of 9.749 > t-table 1.974 and a significant value of 0.000 <0.05. Brand trust has a significant effect on brand loyalty, with a calculated t-value of 12,350 > t-table 1.974 and a significant value of 0.000 <0.05. Based on the results of the F hypothesis test, it can be concluded that simultaneously/together, brand image and brand trust have a significant effect on brand loyalty with an F-value of 121.589 > ttable 3.05 and a significant value of 0.000 <0.05. Based on the coefficient of determination analysis, the coefficient of determination or Adjusted R-Square value was obtained at 0.588 or 58.8% brand image and brand trust have an effect on brand loyalty, while 11.2% is the influence of other variables not included in this study.